Gender Mainstreaming in Education of Bachelors of Humanities in Canadian Universities (Pedagogy of Higher and Secondary Education, 2013)
Iurieva O. Yu. Gender Mainstreaming in Education of Bachelors of Humanities in Canadian Universities.The article deals with the analysis of the main elements in the process of gender mainstreaming in education of bachelors of humanities in Canadian universities. On the basis of curricula analysis in 42 universities in Canada, the key stages and components of the process of gender mainstreaming in education were defined. As a result of reflection on the role of gender mainstreaming in education of bachelors at the departments of humanities in Canada, the structural diagram of the process was developed.
Keywords: gender; gender mainstreaming in education; components of education process; bachelors of humanities